A binding free energy decomposition approach for accurate calculations of the fidelity of DNA polymerases - Rucker, Robert (2010)
DNA polymerase β (pol β) is a small eukaryotic enzyme with the ability to repair short single-stranded DNA gaps that has found use as a model system for larger replicative DNA polymerases. For all DNA polymerases, the factors determining their catalytic power and fidelity are the interactions between the bases of the base pair, amino acids near the active site, and the two magnesium ions. In this report, we study effects of all three aspects on human pol β transition state (TS) binding free energies by reproducing a consistent set of experimentally determined data for different structures. Our calculations comprise the combination of four different base pairs (incoming pyrimidine nucleotides incorporated opposite both matched and mismatched purines) with four different pol β structures (wild type and three separate mutations of ionized residues to alanine). We decompose the incoming deoxynucleoside 5′-triphosphate-TS, and run separate calculations for the neutral base part and the highly charged triphosphate part, using different dielectric constants in order to account for the specific electrostatic environments. This new approach improves our ability to predict the effect of matched and mismatched base pairing and of mutations in DNA polymerases on fidelity and may be a useful tool in studying the potential of DNA polymerase mutations in the development of cancer. It also supports our point of view with regards to the origin of the structural control of fidelity, allowing for a quantified description of the fidelity of DNA polymerases.